THE CONCEPT OF MULTIPLE IDENTITY IN TRANSHUMANIST LITERATURE (THE CASE STUDY OF D. BRIN’S VISION) - Yulia V. Khvastunova (Russian Studies in Culture and Society)
This paper deals with one of the urgent problems in the framework of the implementation of the latest radical technologies of “human enhancement” the so-called theory of multiple identity (multiple “I”, the theory of doubles, and the duplication of consciousness). This topic of a possible backup of our consciousness is analyzed in relation to the procedure for digitally uploading consciousness, creating digital avatars, cyborgs, and clones and cases of success in the field of gene editing as well as the application of this technology to humans. In fiction, particularly in science fiction, this problem is included in the list of top mysterious subjects. As an example, the paper considers a position of a famous science fiction writer and supporter of transhumanism David Brin, presented in the work “Kiln People”. The article highlights main ideas, possible risks, and negative consequences that the writer is trying to foresee and reveal scenarios for the development of launching a mass duplication of consciousness or creating a technology for implementing a multiple identity of “I”.